2016
DOI: 10.5539/ijef.v8n7p207
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Announcement and Ex-Dividend Effects on Stock Return

Abstract: We study the impact of dividend policy on the stock return by investigating reaction of the stock price on the dividend announcement date and the ex-dividend date. In order to achieve this goal, a sample comprising 1962 observations of dividend-related events from 432 listed companies in Vietnam during the period 2008 to 2015 is chosen to analyze and the event study methodology is used to estimate abnormal returns to the shares around the announcement date and the ex-dividend date. Our results clearly show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
2
13
0
6
Order By: Relevance
“…Based on Weng, Chin, Yee, Ann, and Leng (2010) research in Malaysia and Singapore, the results showed that abnormal returns were significant to the dividend announcement. The same results were also revealed by Suwanna (2012) in Thailand, Laabs and Bacon (2013) in America, Kadioglu, Telceken, and Ocal (2015) in Turkey, Ngoc and Cuong (2016) in Vietnam, and Damayanti and Pratama (2018) in Indonesia. Meanwhile, research conducted by Md.…”
Section: Introductionsupporting
confidence: 67%
“…Based on Weng, Chin, Yee, Ann, and Leng (2010) research in Malaysia and Singapore, the results showed that abnormal returns were significant to the dividend announcement. The same results were also revealed by Suwanna (2012) in Thailand, Laabs and Bacon (2013) in America, Kadioglu, Telceken, and Ocal (2015) in Turkey, Ngoc and Cuong (2016) in Vietnam, and Damayanti and Pratama (2018) in Indonesia. Meanwhile, research conducted by Md.…”
Section: Introductionsupporting
confidence: 67%
“…Rosario and Chavali (2016) narrated that the post-event average abnormal returns (AAR) and cumulative average abnormal returns (CAAR) had a significant pattern in Oman stock exchange. Jahfer (2016) and Ngoc and Cuong (2016) also provided evidence for dividend signaling theory in Vietnam and Colombo Stock Exchange, respectively. Similarly, the outcome of Swarnalatha and Babu's (2017) and Ozo and Arun's (2019) studies confirmed the signaling hypothesis as well.…”
Section: Literature Reviewmentioning
confidence: 91%
“…For this purpose, the researchers use different tools like Z-test and t-test. The popular t-statistic was used by Brown and Warner (1980), Kadıoğlu et al (2015), Mahmood, et al (2011), Mukora (2013), Ngoc and Cuong (2016), Rosario and Chaval (2016), and Uddin and Uddin (2014). The null hypothesis (H 0 ) is that is there no significan change occurring in stock prices around the dividend announcement date.…”
Section: Statistical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melalui hasil pengujian statistik Average Abnormal Return tersebut, ditunjukkan bahwa uji t secara konsisten didukung oleh seluruh uji signifikansi lainnya. Perilaku penurunan harga yang tinggi pada periode waktu tersebut sesuai dengan penelitian Ngoc & Cuong (2016) dan Raymond (2017). Seperti yang telah diketahui bahwa periode waktu t+1 dari tanggal cum-dividend merupakan tanggal exdividend.…”
Section: Hasil Dan Pembahasanunclassified